Performing difference, longing for 'home': Claiming ethnic identities to build national unity among urban Solomon Islands youth. (31st July 2022) - Hicks, Rachel Emerine
Abstract: Since independence, Solomon Islands schools have aimed to establish a national identity and unity among Solomon Islanders; however, ethnic ties to 'home' remain strong. This is particularly evident in Honiara, the densely populated and multi‐ethnic capital of Solomon Islands, when urban youth who have grown up in Honiara claim their home is in a province. This paper argues that the 'unity in diversity' narrative taught in schools emphasises the importance of an ethnic identity tied to one's province. As a result, students must find ways to build connections to home, even if they have spent little time there, creating a nostalgia for home. Two ways this occurs is through the dances they perform and the kastom jewellery they wear. I argue that the emphasis of their unique ethnic identities is necessary for youth to stake a claim in the multi‐ethnic urban landscape and within the panethnic identity of Solomon Islander.